Flavonoid Hesperidin Induces Synapse Formation and Improves Memory Performance through the Astrocytic TGF-β1 - Matias, Isadora; Diniz, Luan P.; Buosi, Andrea; Neves, Gilda; Stipursky, Joice; Gomes, Flávia Carvalho Alcantara (Frontiers in Aging Neuroscience, 2017)
Synapse formation and function are critical events for the brain function and cognition. Astrocytes are active participants in the control of synapses during development and adulthood, but the mechanisms underlying astrocyte synaptogenic potential only begun to be better understood recently. Currently, new drugs and molecules, including the flavonoids, have been studied as therapeutic alternatives for modulation of cognitive processes in physiological and pathological conditions. However, the cellular targets and mechanisms of actions of flavonoids remain poorly elucidated. In the present study, we investigated the effects of hesperidin on memory and its cellular and molecular targets in vivo and in vitro, by using a short-term protocol of treatment. The novel object recognition test was used to evaluate memory performance of mice intraperitoneally treated with hesperidin 30 min before the training and again before the test phase. The direct effects of hesperidin on synapses and astrocytes were also investigated using in vitro approaches. Here, we described hesperidin as a new drug able to improve memory in healthy adult mice by two main mechanisms: directly, by inducing synapse formation and function between hippocampal and cortical neurons; and indirectly, by enhancing the synaptogenic ability of cortical astrocytes mainly due to increased secretion of TGF-β1 by these cells. Our data reinforces the known neuroprotective effect of hesperidin and, by the first time, characterizes its synaptogenic action on the CNS, pointing astrocytes and TGF-β1 signalling as new cellular and molecular targets of hesperidin. Our work provides not only new data regarding flavonoid's actions on the CNS but also shed light on possible new therapeutic alternative based on astrocyte biology.